DNA damage from long-term occupational exposure to extremely low frequency electromagnetic fields among power plant workers - Bagheri Hosseinabadi, Majid; Khanjani, Narges; Mirzaii, Mehdi; Norouzi, Pirasteh; Atashi, Amir (Mutation research, 2019)
•Exposure to extremely low frequency electromagnetic fields induced DNA damage in peripheral mononuclear blood cells.•There was a dose-response relationship between magnetic fields exposure and DNA damage and apoptosis.•No significant DNA damage and apoptosis were observed in peripheral mononuclear blood cells due to electrical fields exposure. Extremely low frequency electromagnetic fields (ELF-EMFs) are not known as definite occupational carcinogens, but some studies have reported the genotoxic effects of these fields on cell lines. The present study aimed to evaluate the effects of long-term occupational exposure to these fields on DNA damage. In this cross-sectional study, blood samples were taken from 102 thermal power plant workers as the exposure group and 136 subjects as the unexposed group. DNA damage was evaluated using alkaline comet assay and flow cytometry. Exposure to ELF-EMFs was measured based on spot measurements and the IEEE Std C95.3.1 standard. The indices of comet assay, tail DNA percent, tail factor (%), and damage index were significantly higher in the exposed group compared to the unexposed group. Increased exposure to magnetic fields enhanced comet assay indices, except tail length; while exposure to electric fields had no significant effect on such indices. The percentage of cells at early apoptosis and late apoptosis phases caused by exposure to magnetic fields, respectively, decreased and increased significantly. Long-term occupational exposure to ELF-EMFs can probably cause genotoxic effects.